2020
DOI: 10.3988/jcn.2020.16.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Derivation of Continuous Positive Airway Pressure Settings: Comparison with In-Laboratory Titration

Abstract: Background and PurposeThis study was designed to investigate differences in the final recommended pressure setting between that derived from an autotitrating continuous positive airway pressure (APAP) device and manual in-laboratory continuous positive airway pressure (CPAP) titration, as well as the factors that influence pressure differences in patients with obstructive sleep apnea (OSA). MethodsThis study enrolled 50 patients with OSA. All patients underwent both APAP titration and manual CPAP titration. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…Figure 1 shows information usually not provided in the literature and consists of the histogram of the actual pressure settings for nasal CPAP retained for treating 16,780 unselected patients who underwent conventional CPAP titration in the area of Catalonia, Spain. These data reveal that the mean (±SD) of CPAP pressures retained for the treatment of this large cohort of patients was 9.3 ± 1.7 cmH 2 O, and constitute pressure settings that are remarkably similar to those reported in many research studies involving smaller numbers of patients who were selected/excluded according to specific criteria [ 13 , 14 ]. Most interestingly, the real-life data in Figure 1 indicate that 67.4% of patients are treated with CPAP values within a range of 8–10 cmH 2 O, i.e., differing by only ±1 cmH 2 O from the mean of 9 cmH 2 O.…”
Section: Data On Conventionally Prescribed Cpap In Osasupporting
confidence: 81%
“…Figure 1 shows information usually not provided in the literature and consists of the histogram of the actual pressure settings for nasal CPAP retained for treating 16,780 unselected patients who underwent conventional CPAP titration in the area of Catalonia, Spain. These data reveal that the mean (±SD) of CPAP pressures retained for the treatment of this large cohort of patients was 9.3 ± 1.7 cmH 2 O, and constitute pressure settings that are remarkably similar to those reported in many research studies involving smaller numbers of patients who were selected/excluded according to specific criteria [ 13 , 14 ]. Most interestingly, the real-life data in Figure 1 indicate that 67.4% of patients are treated with CPAP values within a range of 8–10 cmH 2 O, i.e., differing by only ±1 cmH 2 O from the mean of 9 cmH 2 O.…”
Section: Data On Conventionally Prescribed Cpap In Osasupporting
confidence: 81%
“…The median optimal PAP requirement reported in this study tended to be higher than that reported in the literature. [ 21 22 ] This may be attributed to the majority of participants in the study using oronasal masks during the PAP titration polysomnography. [ 23 24 ] Nonetheless, we found a direct relationship between the optimal PAP requirement and OSA severity, as has been suggested in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos não encontraram diferenças estatisticamente significativas entre as pressões médias de tratamento obtidas pela titulação domiciliar com APAP ou com a titulação manual em laboratório de sono. (110,(161)(162)(163) Uma meta-análise englobando 10 ensaios clínicos randomizados comparou o uso da pressão positiva usando titulação domiciliar com APAP versus titulação de pressão positiva no laboratório: não houve diferenças clinicamente significativas na adesão, sonolência ou qualidade de vida entre os grupos. (150) Um ensaio clínico randomizado avaliou a preferência do paciente em relação à conduta diagnóstica/terapêutica no laboratório versus no domicílio, sendo que 62% dos participantes randomizados para o laboratório teriam preferido o manejo domiciliar em comparação com 6% dos participantes no grupo ambulatorial que teriam preferido o manejo laboratorial.…”
Section: Indivíduos Adultos Comunclassified